Exam Crazy: India and the World - Altbach, Phillip; Mathews, Eldho (International Higher Education, 2025)
High-stakes entry examinations for higher education are common worldwide. Recent testing scandals have brought some of the problems related to these tests to the global spotlight. The ubiquitous Chinese gaokao university entrance test is well known, but India’s plethora of tests for entry into many academic institutions and jobs is also important. Recent testing scandals have created problems in India and beyond.